A formulation of industrial conceptual design optimization problem for commercial transport airplanes with turboelectric propulsion - Takami, Hikaru; Obayashi, Shigeru (Frontiers in Aerospace Engineering, 2023)
A conceptual design optimization problem for commercial transport airplanes with turboelectric propulsion, with a reasonable fidelity and comprehensiveness suitable for industrial purposes, is formulated, in order to allow for proper assessment of the benefits of turboelectric propulsion. As a sample problem, we carry out conceptual design optimization of a turboelectric propulsion airplane concept in a conventional tube-and-wing configuration with a turbofan and an associated electric fan on each (i.e., left and right) wing, varying the performance of the turboelectric propulsion devices. The results indicate that proper assessment of the benefits of the turboelectric propulsion can be carried out using the formulated optimization problem. The findings from the sample problem, including notable benefits of the turboelectric propulsion and the performance crossover point where the fuel efficiency of an airplane with conventional propulsion and that of an airplane with turboelectric propulsion cross over, are also presented.